The Effect of Occupational Safety and Health on Employee Productivity at PG Wringin Anom Situbondo - Niatilla, Sawilda; Kurniawati, Dewi; Ardi, Aditya Nizar Al; Saadillah, Dinu (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2023)
The use of machine and tools in productivity process is very important. The risk of occupational accidents increases when employees work using machine and tools, so it is essential for a company to apply occupational safety and health to prevent the accidents while working. This study was conducted at PG. Wringin Anom Situbondo especially in installation. Data collection methods used in this study were observation, questionnaire, interview, and literature studies. A number of respondents was 49 respondents. Analytical techniques used were multiple linear regression, coefficient of determination analysis, F test, and t test. Based on the result of test through using of SPSS 16.0 for windows, it can be concluded that (1) variable safety (X1) has significant effect on workforce productivity (Y) of the employees in installation of PG. Wringin Anom Situbondo; (2) Work health variable (X2) has no significant effect on workforce productivity (Y) of the employees in installation of PG. Wrimgin Anom Situbondo; (3) Both of work safety (X1) and work health (X2) have significant effect of workforce productivity (Y) of the employees in installation of PG. Wringin Anom Situbondo; (4) the dominant variable that has significant effect on workforce productivity (Y) of the employees in PG. Wringin Anom Situbondo is work safety (X1).